Implementation od PSAK 19 Zakat, infaq and Shadaqah Accounting in the Badan Amil Zakat Nasional (BAZNAS) Pontianak - Redhea, Yaswinta Ulfa (Jurnal KIAFE, 2023)
This study aims to analyze the application of zakat accounting based on PSAK 109 at the BAZNAS Pontianak. The approach used is researcher use a qualitative method descriptive analysis. The result showed that (1) The accounting process at the BAZNAS Pontianak was not fully in accordance with general accounting theory; (2) Recognition and measurement of zakat on BAZNAS Pontianak was in accordance with PSAK 109; and (3) Presentation and disclosure on BAZNAS Pontianak was not in accordance with PSAK 109.